2013
DOI: 10.1080/18756891.2013.754172
|View full text |Cite
|
Sign up to set email alerts
|

Parameters control in GAs for dynamic optimization

Abstract: The Control of Genetic Algorithms parameters allows to optimize the search process and improves the performance of the algorithm. Moreover it releases the user to dive into a game process of trial and failure to find the optimal parameters. Yet the control of parameters has received much attention in the case of static optimization problems, its investigation in the case of dynamic optimization problems (DOPs) is certainly a promising area of search. Indeed, in the case of DOPs the problem is not just to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It should be noticed here that the idea of feedback-control inspiration constitutes a further step beyond some studies that have considered the theme of parameter adaptation in evolutionary computation. Examples of those studies can be found for instance in Vasconcellos et al (2001), McGinley et al (2011), Lin and Chen (2013), and Jebari et al (2013). The introduction of feedback control concepts in order to state the parameter adaptation procedures allows the recovery, within the field of evolutionary computation, of some well-established results from control theory concerning closed-loop system dynamics and stability.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noticed here that the idea of feedback-control inspiration constitutes a further step beyond some studies that have considered the theme of parameter adaptation in evolutionary computation. Examples of those studies can be found for instance in Vasconcellos et al (2001), McGinley et al (2011), Lin and Chen (2013), and Jebari et al (2013). The introduction of feedback control concepts in order to state the parameter adaptation procedures allows the recovery, within the field of evolutionary computation, of some well-established results from control theory concerning closed-loop system dynamics and stability.…”
Section: Introductionmentioning
confidence: 99%
“…An initial population of potential solutions (in the applications we discuss, a "solution" is an ANN of value in solving a scientific problem) is iteratively improved through fitness-based selection and the generation of diversity. 15 Population-based EAs can create several elements of a Pareto optimal set in a single run when the chance of finding a unique optimal solution is low. 105 The GA, currently the most popular EA, was sketched out by Holland 16,17 and developed by numerous groups.…”
Section: Introduction: Computational Models In Processmentioning
confidence: 99%